GRAPHIC ORGANIZERS IN TEACHING READING AT THE TENTH GRADE OF SMA MUHAMMADIYAH WAY JEPARA - Juni Bayu Saputra (LPPM STAI DARUSSALAM LAMPUNG, 2017)
This research focuses on finding out the improvement of the students? reading skill at the Tenth grade of SMA Muhammadiyah Way Jepara through graphic organizers. Classroom action research (CAR) was implemented in this research which was conducted to solve the students? problem in English reading. The Classroom Action Research (CAR) was done based on Kemmis and McTaggart?s design. The researcher did two cycle in which each cycle consists of planning, acting, observing, and reflecting. The finding of the research indicated that the implementation of graphic organizers was successful since the criteria of success were achieved. The first criterion was 70 % of students could pass the target score 70 based on the KKM. Based on the calculation on table 1, it is known that the mean score of pretest that consist of 32 students is 6.92 and the posttest is 8.27, in other words, it can be said that the use of graphic organizers is effective to improve students' reading comprehension.